ROZLICZENIE KOSZTÓW PODRÓŻY W RAMACH SPÓŁKI A ZAGADNIENIE IMPENSA IN SOCIETATEM I PROPTER SOCIETATEM W ROZUMOWANIU LABEONA I JULIANA - Służewska, Zuzanna (Zeszyty Prawnicze, 2017)
The participation of Partners in Travel Expenses and Losses. impensa in societatem and propter societatem According to Labeo and Julian Summary The problem discussed in this paper regards the participation of partners in travel expenses and losses suffered during a business trip. In the title pro socio of the Digest there are three texts that refer to this question: D. 17,2,52,4 and D. 17,2,52,15 and D. 17,2,60,1. The first one refers to sagaria negotiatio conducted in a form of a partnership and analyses the case of a partner who during a business trip was attacked by robbers who stole his property and injured his slaves. According to Julian (cited by Ulpian) all those losses (even all what was paid to a doctor for the treatment of the slaves) should be shared by all partners. The second text also refers to the expenses incurred by one of the partners during a business trip that should be shared with the other partner. The third one concerns the problem of sharing the expenses incurred for the medical treatment by one of the partners that had been wounded while trying to prevent the slaves, who were their common property, intended for sale from escaping. According to Labeo, in this case the part of the money spent on a doctor could not be claimed from the other partner as it was not spent in societatem but propter societatem. The main question discussed in relation to the above mentioned texts concerns the disagreement between Julian and Labeo in the matter of sharing the expenses incurred for the medical treatment in a partnership. This question has been widely discussed and analysed from various points of view among the Romanists (Gandolfi, Santucci, Meissel) who tried to explain the concept of impensa in and propter societatem and thus found some reasonable justification for the negative decision made by Labeo. In my opinion the case discussed by Labeo should be analised in relation to other texts focused on the problem of determining the limits of a common activity or a common patrimony in a partnership other than a societas omnium bonorum, as for example the texts of D. 17,2,58 pr.-1 or D. 17,2,52,4. Those texts clearly show the problems discussed by Roman jurists at the moment of the evolution from the traditional form of partnership societas omnium bonorum (based on the total community of all partners’ patrimonies) into a more limited form of partnership treated as an instrument of conducting an economic activity. Particularly in D. 17,2,58 pr., Celsus made a clear distinction between a partnership established for the purpose of “having” goods in common and “selling” goods in common which corresponds to the distinction between „società di mero godimento” based on the schema of societas omnium bonorum (and thus total community of all profits and losses) and „società questuarie” aimed to gain profits from some kind of an economic activity in which only the profits and losses resulted from conducting the common business were to be shared among partners). Consequently in a partnership established for the purpose of “having” goods in common all the losses that regarded the common patrimony were to be shared while in a commercial partnership losses not resulting from a partnership’s activity (even regarding the common patrimony) were not shared. From the analysis of those texts we could also deduce that in case of a partnership with a limited scope in order to determine whether some losses suffered by one of the partners should be shared it was crucial whether they would not have been suffered if the partnership had not existed. We could suppose that Labeo in D. 17,2,60,1 analysing the case of a wounded partner, used a similar scheme of thinking. In the case discussed by this jurist the slaves were the property of the partners but the aim of the partnership was to sell them and not to posses them. That is why even if the partnership had not existed their owner would have tried to impede their escape and as a consequence would have had to pay a the doctor’s fees. Thus one could not say that the loss suffered by the injured partner would not have been suffered if the contract of partnership had not been concluded and for this reason Labeo did not permit to claim its reimbursement from the other partner. The hypotheses that the problem discussed by Labeo should be interpreted from the point of view of the distinction between a universal type of a partnership and a partnership with a limited scope is also confirmed by the final part of the text of D. 17,2,60. Labeo, for making the distinction between the costs defined as spent in societatem and propter societatem clearer, mentioned other kinds of profits and losses that were to be shared only in a partnership omnium bonorum aimed to possess and administer goods in common, but were not shared in a partnership with a limited scope established for a purpose of buying and selling goods.